A graphene oxide layer as an acid-resisting barrier deposited on a zeolite LTA membrane for dehydration of acetic acid. Issue 28 (29th February 2016) - Xu, Kai; Jiang, Zhenqi; Feng, Bo; Huang, Aisheng
Abstract : A graphene oxide layer (GO) was deposited as acid-resisting barrier to avoid the degradation of zeolite LTA membrane by acetic acid, leading to a high selectivity and stability of the zeolite LTA membrane for the dehydration of acetic acid. Abstract : It is well known that zeolite LTA membranes have poor acid resistance although they have been considered the best hydrophilic zeolite membranes for the dehydration of organic aqueous mixtures. In the present work, we develop a simple and effective road to enhance the acidic stability of the zeolite LTA membrane through the depositing of a graphene oxide (GO) layer as an acid-resisting barrier on the surface of the zeolite LTA membrane. A relatively thin (about 5.5 μm) but dense and firm LTA@GO composite membrane is obtained by using dopamine as a covalent linker between the zeolite LTA and GO layers. The presence of the protective GO layer effectively inhibits the degradation of the zeolite LTA membrane by acetic acid, which greatly enhances its acid-resistant stability, leading to a high selectivity and stability for the dehydration of acetic acid. For the separation of 95 wt% acetic acid/water mixture at 333 K, the separation factor and flux of the LTA@GO composite membrane are about 400 and 1.5 kg m −2 h −1, respectively, and keep almost constant for 168 h.